TECHNICAL EFFICIENCY ANALYSIS OF SUGAR CANE FARMING IN MALANG REGENCY, INDONESIA - Pujiastuti Lestari; Nuhfil Hanani; S Syafrial (Agricultural Socio-Economics Journal, 2019)
This research aimed to analyze the factors that affect the production of sugar cane, to analyze the level of technical efficiency of farming sugar cane, and to analyze the factors that affect the technical inefficiency of sugar cane farming in Malang Regency. Methods of data analysis that is used to find out the factors that affect the production of sugar cane and the level of technical efficiency of sugar cane farming is a stochastic frontier analysis used  the Frontier 4.1 software. As for knowing the factors  that affect technical inefficiency of sugar cane farming used tobit regression analysis. The results show that production factors of sugar cane farming in Malang Regency i.e. amount of seeds, amount of labor, amount of fertilizer, amount of land area, and ratooncane. The average technical efficiency of sugar cane farming achieved i.e 0,81. Factors that influence the technical inefficiency of sugar cane farming i.e. age factors of farmers and formal education have a positive influence on the inefficiency effect of sugar cane farming and factors of farm experience and farmer group participation have a negative effect on the inefficiency effect of sugar cane farming.